Cytokine Gene Expression and Treatment Impact on MRI Outcomes in Jordanian Patients with Multiple Sclerosis - Sawsan I. Khdair; Mohammed Waleed; Alaa M. Hammad; Lubna Al-Khareisha; Tariq Jaber; Majd Ayash; Frank Scott Hall (Life)
Background: Central nervous system autoimmune disorders, like multiple sclerosis (MS), are chronic conditions where cytokines contribute significantly to the regulation of inflammation. The diagnosis, progression, and treatment effectiveness of MS are assessed through laboratory tests and clinical evaluation, as well as imaging. Method: This study included 40 healthy individuals as a control group and 75 MS patients, divided into two groups: 45 MS patients receiving fingolimod treatment (MSW) and 30 patients taking other medications (MSOs). Blood samples (3 mL) were collected from all participants, and the mRNA relative expression of cytokine genes (IL-1β, TNF-α, IL-6, and INF-γ) was measured. Additionally, MRI images of MS patients undergoing fingolimod or other treatments were analyzed. Results: The MSO patient group displayed higher mRNA expressions of IL-1β, TNF-α, IL-6, and INF-γ compared to the control group. Furthermore, TNF-α, IL-6, and INF-γ expressions were elevated in the MSO group compared to the MSW group. MRI scans showed significant improvement in MS patients taking fingolimod compared to those receiving other medications. Conclusions: Fingolimod demonstrated greater effectiveness in improving MS patients’ conditions, possibly due to its impact on cytokine expression.